Role of Environmental Concern towards Purchase Intention in Organic Food Product Consumption - Shamsudin, Mohd Farid; Basha, Mohamed Bilal; Mason, Cordelia; Hussain, Hafezali Iqbal; Salem, Milad Abdelnabi; Ahmad, Zulkarnian (International Journal of Engineering and Technology, 2018)
The awareness level of consuming healthy products such as organic based has been increased. Consumers are also particular about the environmental that associated to the products.Â Positive attitude towards environment is important factor in the purchase intention towards the organic food products where it motivates the consumer towards the purchase intention. A total of 1300 questionnaire were distributed randomly to the potential target respondents who were basically consumers of large supermarkets. Results revealed a significant relationship between environmental concerns towards the purchase intention of organic food products.